Losartan as a Steroid-Sparing Adjunct in a Patient With Features of Refractory Camurati-Engelmann Disease - Khushboo Agarwal, MD; Remya Rajan, MD; Jinson Paul, MD; Kripa Elizabeth Cherian, MD, DM, DNB; Nitin Kapoor, MD, DM, PhD; Thomas V. Paul, MD, DNB, PhD (AACE Clinical Case Reports, 2022)
Objective: The treatment of Camurati-Engelmann disease (CED) involves the use of glucocorticoids, analgesics, and bisphosphonates; experience with the use of losartan is limited. Our objective was to describe the case of a patient diagnosed with CED whose symptoms remained refractory while on steroids and bisphosphonates and who was successfully treated with losartan. Case Report: A 27-year-old woman presented with bone pain involving her extremities and large joints for 1 year. Clinical examination revealed bone tenderness and proximal myopathy with elevated C-terminal peptide of type 1 collagen (1617 pg/mL; normal range, 137-573 pg/mL) and N-terminal propeptide of type 1 procollagen levels (163 ng/mL; normal range, 5.1-58.3 ng/mL). Calcium (9.4 mg/dL; normal range, 8.3-10.4 mg/dL), phosphate (3.4 mg/dL; normal range, 2.5-4.5 mg/dL), and parathyroid hormone (62 pg/mL; normal range, 8-80 pg/mL) levels were within the normal range. Radiographs showed hyperostosis involving the diaphyseal region of long bones of the lower and upper limbs, and a provisional diagnosis of CED was made. She was treated with prednisolone, 30 mg daily, with which she reported some improvement. As exogenous Cushing syndrome had developed in her because of prednisolone, its dose was tapered. Subsequently, her bone pain worsened. Thereafter, she was initiated on oral alendronate. Due to persistent pain, losartan was added, after which she had marked decrease in bone pain with a reduction in the C-terminal peptide of type 1 collagen (375 pg/mL) and N-terminal propeptide of type 1 procollagen (50 ng/mL) levels. Discussion: Occasionally, CED presents therapeutic challenges, and when its symptoms remain refractory to conventional doses of steroids and bisphosphonates, other options may be needed. The abovementioned patient was initiated on losartan, which acts by downregulation of transforming growth factor β1, leading to the reduction in pain. Conclusion: Losartan downregulates transforming growth factor β1 and may be offered as a steroid-sparing option in individuals diagnosed with CED if symptoms remain refractory to conventional treatment.